Ministerial Decree No. 727/2014 Enforcing Some Provisions of Law No. 371/195 On Public Shops and Law No. 372/1956 On Entertainment Places = قرار وزاري رقم 727 لسنة 2014 بتنفيذ بعض أحكام القانون رقم 371 لسنة 1956 في شأن المحال العامة والقانون رقم 382 لسنة 1956 في شأن الملاهي / Prime Minister - Egypt. Prime Minister (2025)
Ministerial Decree No. 727/2014 Enforcing Some Provisions of Law No. 371/195 On Public Shops and Law No. 372/1956 On Entertainment Places قرار وزاري رقم 727 لسنة 2014 بتنفيذ بعض أحكام القانون رقم 371 لسنة 1956 في شأن المحال العامة والقانون رقم 382 لسنة 1956 في شأن الملاهي